Two new species of Microlicia (Melastomataceae) from Chapada Diamantina, Bahia, Northeastern Brazil - Gali, Lorena; Pacifico, Ricardo; Almeda, Frank; Fidanza, Karina (Phytotaxa, 2022)
Microlicia is a Neotropical genus with about 245 species centered in central-eastern Brazil, in areas of campo rupestre and Cerrado. The majority of species occur in the states of Minas Gerais, Bahia, and Goiás. Based on specimens from the herbaria ALCB, HUEFS, MBM, SPF, HUFU, and US, we here describe two new species from the Chapada Diamantina region, Microlicia decumbens and Microlicia macaubensis. Microlicia decumbens is apparently endemic to Abaíra municipality, whereas M. macaubensis is known only from Brotas de Macaúbas municipality. We provide morphological descriptions, line drawings, a distribution map, and comparisons with putative relatives for both species.